Dar Kochen Bad Miayad - Yazdani, Diako (Iran : Setak Film Sanandaj, 2008)
A teenage boy selling saplings enters a dry and treeless town. Unable to find customers, he faces strange and bizarre reactions from the residents. Shot in two days, the film is a covert look at poverty, child labor and trees.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films